Hypoxemia associated with lumbar puncture in neonates - Sharma, Tripti; Ajmera, Mohit; Sharma, Gopikishan; Mayenger, Amrita (Indian Journal of Child Health, 2021)
Objectives: The objectives of the study were to study the effect of different stages of lumber puncture (LP) procedure on oxygen saturation (SpO2) in newborn baby. Materials and Methods: It was a 1-year, prospective observational study conducted in a tertiary care hospital. Forty neonates were included who fulfilled the inclusion criteria. SpO2 was measured during the different stages of LP in the recruited newborns and comparison was done between SpO2 changes in LP duration of 5 min versus 5 min group during flexion and needle insertion phase. Hypoxemia is more in preterm than term neonates during flexion and during needle insertion, supine repositioning. Furthermore, hypoxia recovered after 5 min of supine repositioning more in term infants. Conclusions: Significant hypoxia was associated in newborn in flexion and needle insertion phase of lumbar puncture, especially in preterm newborns and those with prolonged duration of procedure.